Oversight, Accountability, or Influence? Understanding the Use of Monetary Dialogues in the European Parliament - Amie Kreppel; Corinne Tomasi (Politics and Governance)
The Monetary Dialogue (MD) between the European Central Bank (ECB) and the European Parliament (EP) has received ample research that has offered an insightful discussion on the effectiveness of the dialogue as a forum for ECB accountability. However, most of the literature has focused on what the ECB is held accountable for or how the ECB engages in the dialogues. Key questions remain, however, regarding the goals and actions of the individual members of the European Parliament (MEPs) that this article seeks to address. First, we develop a theoretical framework that moves beyond a general concept of “accountability” and differentiates between accountability, oversight, and influence. By defining the concepts more precisely, our aim is to distinguish types of engagement and offer a comparative perspective to broaden the discussion of accountability forums. Second, our article contributes to a growing subset of literature on the MD that shifts the focus from what the ECB gets from the dialogues to how MEPs utilize the MD. To achieve this, we analyze and code MEP questions during the quarterly MD and investigate the impact that member state, national party, and EP political group affiliation have on the character of the questions asked by MEPs over time.